Development of multi-stimuli responsive shape memory composite materials for 4D printing - Muir, Kyle Deen (Nanyang Technological University, 2024)
Four-dimensional (4D) printing has emerged as a transformative technology, enabling the creation of dynamic structures that evolve over time in response to external stimuli. This study investigates how to utilise 4D printing technology with functional fillers such as graphene oxide (GO) and carbon nanotubes (CNTs), together with thermoplastic polyurethane (TPU) to produce printed structures that can change their shapes under external stimuli. Comprehensive material characterizations were carried out by varying the weight percentages of GO and CNT to evaluate the mechanical, thermal, electrical, and shape memory properties of the composite materials. In addition, the project aims to develop a multi-stimuli component that can respond to different environmental stimuli. The results emphasise the role of GO and CNT in improving the strength, electrical conductivity, and heat absorption rate of the TPU matrix. The research results provide valuable insights for the future optimisation of the composition of 4D-printed materials suitable for various applications in aerospace, biomedical engineering, and smart textiles. Overall, this study contributes to the development of dynamic and adaptable materials that respond individually to different stimuli and demonstrates the potential of 4D printing technology in the development of functional materials.